Penegakan Hukum Terhadap Pelaku Tindak Pidana Pembunuhan (Putusan Nomor 312/Pid.B/2023/PN Amb) - Samangun, Indriyani; Sopacua, Margie Gladies; Latumaerissa, Denny (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The crime of murder is a serious violation of the fundamental right to life. Often, these crimes are triggered by the consumption of alcoholic beverages, which affects the perpetrator's control. This was observed in Case Number 312/Pid.B/2023/PN Amb, where the defendant stabbed the victim while under the influence of alcohol.Purposes of the Research: This study aims to analyze the law enforcement process and the judge's legal considerations in sentencing the perpetrator of murder under the influence of alcohol in the decision Number 312/Pid.B/2023/PN Amb.Methods of the Research: This research uses a normative juridical method with a statutory, case, and conceptual approach. The data used are secondary data obtained through library research and analyzed qualitatively.Results / Findings / Novelty of the Research: The results show that the law enforcement process has proceeded in accordance with the Criminal Procedure Code (KUHAP). The judge considered the elements of Article 338 of the Criminal Code to be proven. However, in the sentencing considerations, the judge used the defendant's drunkenness and spontaneity as mitigating factors, resulting in a sentence of 8 years in prison. This is considered relatively light compared to the maximum threat of 15 years and the fatal consequence of the loss of life, raising questions about the balance between legal certainty and substantive justice